Progress In Motor Learning Through Augmented Feedback (video Feedback From A Model And Video Feedback From Its Own Realization), The Case Of The Long Jump Technics. - Chettouh, Farid; Hadji, Abderrahmene; Bougandoura, Fares (sports creativity, 2025)
The aim of this study is to test the effect of an augmented feedback device composed of video feedback associated with verbal feedback on an entire class, while learning a new task in physical education and sport (PSE). This device is put in place for six weeks during a long jump cycle with a class of second year secondary. The experimental method was used to suit the nature of the research, where the sample included 26 students divided into two groups of equivalent level composed of thirteen (13 boys and girls) each. Group1 received verbal feedback and video feedback, (viewing their own performance).Group2 received verbal feedback and video feedback (viewing a model ). The results show on the one hand that video feedback facilitates and accelerates the improvement of motor progress among all the pupils of the two groups. Thus, it corroborated the various researches carried out to date on the usefulness of video feedback, and others share a more significant progression in learning in the group 1 VPR (viewing their own performance), than in the group 2 VM (viewing a model)